O pensamento de Antonio Gramsci e as possibilidades de revolução passiva ou efetiva no capitalismo do século XXI - Curro, Carlos Augusto de Godoy (2014)
This dissertation aims to critically analyze the main characteristics of capitalism in the twenty-first century considering the theories of Italian philosopher Antonio Gramsci, in order to contribute to the identification of specific possibilities for change in the contemporary social relations of production. Within the historical context that has developed from the fall of the Berlin Wall, this work considers the progress of cultural and ideological domination of the capitalist system, the increasing complexity of civil society and the current relevance of concepts and strategies proposed by Gramsci, in particular hegemony, war of position, integral state, passive revolution - in its contemporary strand - and intellectual and moral reform. Finally, an analysis of the alternatives of counter-hegemonic struggle is made, describing the contradictory results of reformism as adopted by the contemporary left in the fight for power in political society, and the importance of an organic and expanded process of education as an essential step in building a new hegemony to overcome the current economic model, enabling an effective and wide revolution that results in a new society.